The price effects of cross‐market mergers: theory and evidence from the hospital industry. (10th April 2019) - Dafny, Leemore; Ho, Kate; Lee, Robin S.
Abstract: We consider the effect of mergers between firms whose products are not viewed as direct substitutes for the same good or service, but are bundled by a common intermediary. Focusing on hospital mergers across distinct geographic markets, we show that such combinations can reduce competition among merging hospitals for inclusion in insurers' networks, leading to higher prices (or lower‐quality care). Using data on hospital mergers from 1996–2012, we find support that this mechanism operates within state boundaries: cross‐market, within‐state hospital mergers yield price increases of 7%–9 % for acquiring hospitals, whereas out‐of‐state acquisitions do not yield significant increases.